PENDAMPINGAN PRAKTIK BERWUDHU BAGI ANAK-ANAK DI LINGKUNGAN MASJID AL-JIHAD DESA KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR PROVINSI RIAU - Hasan Hasan (Abdimas Aswaja: Jurnal Pengabdian Masyarakat, 2025)
Ablution is a process of cleanliness carried out by a person to wash the parts of the body that have been determined. Wudhu itself consists of two aspects of cleanliness; namely cleanliness related to the physical aspect and the inner aspect caused by the effect of wudhu on humans in the form of cleansing from mistakes and sins committed by the members of the body. The formulation of the problem of this study is “Why most children in the Al-Jihad Mosque neighborhood cannot perform wudu perfectly?” This activity aims to “carry out guidance for children in the Al-Jihad Mosque neighborhood so that they can perform wudu perfectly”. The assistance and training program prepared is an aspect of the field of community service, therefore the method used in the implementation of ablution training for children in the Al-Jihad Mosque Environment, Kubang Jaya Village, Siak Hulu District, Kampar Regency, Riau Province. The results of community service activities carried out on Sunday Date, November 03, 2024 followed by children in the Al-Jihad Mosque environment are in accordance with the planned targets. Conclusion Based on the results of the activities of assisting the practice of ablution for children in the Al-Jihad Mosque Environment, Kubang Jaya Village, Siak Hulu District, Kampar Regency, Riau Province, they were very enthusiastic in participating in all stages of this community service activity and the opening of insights and scientific treasures of children in the al-Jihad Mosque environment according to the results of the community service activities.